Five-Year Plan for Bijapur District (1951-52 To 1955-56) Government of Bombay - Planning Commission (Planning Commission, 1951)
After the merger of the States, the State areas could not be conveniently and efficiently administered by two Brants as the areas, population and revenue vastly increased and the State areas had their own peculiar problems. Accordingly a thud Brant was created with Head Quarters at Jharkhand comprising of Jharkhand and Mudhol Talukas and Bilgi Betha. There were therefore three sub-divisions in the Bijapur District: Bijapur subdivision consisting Bijapur, Bagewadi, Indi and Sindgi Talukas.
Government of Bombay